STRATEGI PENGUATAN NILAI-NILAI PANCASILA MELALUI INOVASI PEMBELAJARAN PKN BERORIENTASI CIVIC KNOWLEDGE,CIVIC DISPOSITION, DAN CIVIC SKILL DI PERGURUAN TINGGI - Muchtarom, Moh. (PKn Progresif, 2012)
research produced strategy the Pancasila values reinforcement through the innovation of Civic Knowledge-, Civic Disposition-, and Civic Skill- Oriented Civic Education Learning. Such the strategy built on the renewal of existing content in Civic education course. The reinforcement strategy obtained by studying the conceptual theoretical framework in ontological hierarchy of Civic Education at College through studied object in which the ideal, instrumental and practical aspects were examined. In this research, the ideal aspect was the study on Civic Education regulation policy at College; instrumental aspect was the content of Civic Education at college, while practical aspect was the potential challenge or threat of the Pancasila values implementation in life, Pancasila values reinforcement in Civic Education, and Civic Education problems emerging at college. This research was conducted in both public and private college in Solo City with lecturers and students as the subject of research. This study was a descriptive philosophical qualitative This research. The data collection was conducted by interviewing the practitioners and lecturers relevant to the research, observing the lecturers and students in Civic Education learning process, studying the document relevant to Civic Education policy, and holding Focus Group Discussion with experts, lecturers and students. The data validation was done by improving the persistence of conducting research, triangulation, observation extension, discussion and theoretical study. The data obtained was then processed through reduction, analysis process and presented qualitatively. The conclusions of research were 1) the presence of potential challenge and threat against the implementation of Pancasila values in life deriving externally that was primordial in nature (ethnic, race, religion), externally by the presence of globalization development, the presence of external factor of western ideology affected both directly and indirectly the nation life. 2) The Pancasila values reinforcement strategies in Civic Education at college included renewing the content of Civic education by strengthening the Civic Education  core in each substance of study; thereby in its development, each substance of study was inspired by the Pancasila values philosophically. 3) The form of innovation or renewal for reinforcing the Pancasila values in Civic Education was the further extension of the Pancasila values reinforcement strategy in Civic Education course in the form of standard product, the substance of which was inspired by the Pancasila values as the core of Civic Education.